Occult neck metastases risk factors and the role of elective neck dissection in cT3-4N0 adenoid cystic carcinoma of the parotid gland - Yuan, Junhui; Meng, Fan; Xu, Chunmiao; Li, Wenlu; Wu, Shuang; Li, Hailiang (Frontiers in Oncology, 2022)
Background Objectives: To determine the predictor for occult neck metastases and the role of elective neck dissection (END) in cT3-4N0 parotid adenoid cystic carcinoma (ACC). Methods: Patients with surgically treated parotid ACC were retrospectively enrolled. Predictors of occult neck metastases and the effect of END on disease specific survival (DSS), overall survival (OS), locoregional control survival (LRC), and distant metastasis free survival (DMS) were analyzed. Results: Occult neck metastases occurred in 35 (19.7%) of the 178 patients undergoing an END. The tumor stage (p=0.011, 4.215 [1.387–10.435]) and intraparotid lymph node metastasis (p=0.032, 3.671 [1.693–8.775]) were related to the possibility of occult neck metastases independently. The END group had better 10-year LRC than the observation group (56% vs. 43%, p=0.002) and also better 10-year DMS than the observation group (43% vs. 32%, p<0.001). The two groups had similar 10-year DSS (40% vs. 33%, p=0.230) and OS (31% vs. 23%, p=0.094) rates. Further, the Cox model confirmed that END was independently associated with better LRC rate (p=0.022, 2.576 [1.338–6.476]) and better DMS (p=0.011, 2.343 [1.274–7.462]). Conclusions: Occult neck metastases in cT3-4N0 parotid ACC was not common. A T4 tumor with intraparotid lymph node metastasis had the highest possibility of occult neck metastases. END had no effect on DSS or OS but significantly decreased the risk of locoregional recurrence and distant metastasis.